Study on Optimum Condition of Empty Fruit Bunch-Graft-Poly (Acrylamide) Superabsorbent Polymer Composites - Goh Mun, Chun (2013)
Superabsorbent polymers (SAPs) are three-dimensional networks of flexible polymer chains that carry dissociated and ionic functional group which characterized by hydrophilicity. Nowadays, many things created by industrial highlighting on environment friendly element, and using EFB which is a natural fiber to produce superabsorbent polymers are the new technique to reduce the pollution. This research is conducted to study on the optimum condition of Empty Fruit Bunch-graft- Poly(acrylamide) Superabsorbent Polymer Composite (EFB-g-PAAm SAPC). The objective of this study is to determine the optimum water absorbency of superabsorbent polymer composite (SAPC) by varied the amount of EFB, initiator, and crosslinker. EFB-g-PAAm was synthesized by graft copolymerization of monomer, acrylamide (AAm) onto EFB backbone with N, N’-methylenebisacrylamide (MBA) and ammonium persulphate (APS) acts as crosslinker and initiator. The method used to determine the water absorbency of SAPC was the tea-bag method. The results showed that optimum water absorbency of effect of filler was achieved at 196.3320 g/g with 5 wt. %. Meanwhile, the optimum water absorbency of effect of initiator and crosslinker were achieved at 218.4060 g/g and 171.2867 g/g when the amount of initiator and crosslinker were 30 wt. % and 10 wt. %, respectively. The chemical structure of the EFB-g-PAAm SAPC was characterized by FTIR spectroscopy and the surface morphological study of EFB-g-PAAm SAPC was conducted by scanning electron microscopy (SEM). Thermogravimetric Analysis (TGA) was carried out to determine the thermal properties of the synthesized superabsorbent polymer composites. In conclusion, the objective of this study has achieved where the optimum condition for the SAPC has been determined. As recommendation, in order to improve the properties of synthesis of EFB-g-poly (acrylamide), some recommendation should be considered such as parallax error needs to be avoided during the measurement of the chemicals.